Dietary supplement increases anagen hair rate in women with telogen effluvium: results of a double-blind, placebo-controlled trial. Issue 1 (January 2007) - Lengg, Nadine; Heidecker, Barbara; Seifert, Burkhardt; Trüüeb, Ralph M
Background: Dietary supplements are traditionally used over-the-counter products for the treatment of hair loss.Objectives: We aim to examine the effect of a specificL -cystine, medicinal yeast, pantothenic acid complex-based dietary supplement (Pantogar ®® ) on telogen effluvium in healthy women.Methods: A randomized, double-blind, placebo-controlled study was conducted over 6 months in 30 healthy women suffering from telogen effluvium. The efficacy of the supplement was evaluated by means of digitalized epiluminescent microscopy (TrichoScan) performed before treatment and after 3 and 6 months. Additionally, global photographs were taken and evaluated by independent investigators.Results: Active compound led to a statistically significant improvement and normalization of the mean anagen hair rate within 6 months of treatment (p = 0.003), while there was no significant change in the placebo group (p = 0.85). These changes of the anagen hair rates were significantly different (p = 0.008). The appearance of hair growth in the global photographic assessment was judged better in the active compound than in the placebo group.Conclusions: This is the first study performed combining epiluminiscence microscopy with digital image analysis to demonstrate that a dietary supplement influences hair growth. The mode of action is not known, although it seems to result from an induction of anagen.